Hambatan Penegakan HAM Terhadap Kesetaraan Gender Di Dunia Kerja Dalam Budaya Patriarki - Muhammad Edwar (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
The issue of gender equality is still a crucial issue in upholding human rights in Indonesia, especially considering the strong patriarchal culture. Although there has been progress in policies and regulations, there are still obstacles in achieving equality in the work environment. This study examines in depth how patriarchal culture affects the implementation of human rights principles related to gender equality in the world of work. Through analysis of the existing legal framework including Law No. 39/1999 on Human Rights. Through a juridical-normative approach, this research shows a paradox between the existence of a progressive legal framework and the reality of gender discrimination that still occurs in the world of work. This indicates the existence of obstacles to gender equality, most of which are rooted in patriarchal culture. This research concludes that there is a need for legal harmonization, strengthening of enforcement mechanisms, and integration of gender perspectives and policy implementation to overcome these barriers. This research contributes to the development of more effective legal strategies in realizing gender equality in the world of work, in line with human rights principles and social justice ideals.